The cylindrical GEM detector of the KLOE-2 experiment. (11th July 2017) - Bencivenni, G.; Branchini, P.; Ciambrone, P.; Czerwinski, E.; De Lucia, E.; Cicco, A. Di; Domenici, D.; Felici, G.; Fermani, P.; Morello, G.
Abstract: The KLOE-2 experiment started its data taking campaign in November 2014 with an upgraded tracking system at the DA Φ NE electron-positron collider at the Frascati National Laboratory of INFN. The new tracking device, the Inner Tracker, operated together with the KLOE-2 Drift Chamber, has been installed to improve track and vertex reconstruction capabilities of the experimental apparatus. The Inner Tracker is a cylindrical GEM detector composed of four cylindrical triple-GEM detectors, each provided with an X-V strips-pads stereo readout. Although GEM detectors are already used in high energy physics experiments, this device is considered a frontier detector due to its fully-cylindrical geometry: KLOE-2 is the first experiment benefiting of this novel detector technology. Alignment and calibration of this detector will be presented together with its operating performance and reconstruction capabilities.